E-government in Lithuania – local self-government layer - Raginytė, Elena; Paliulis, Narimantas Kazimieras (Business, Management and Economics Engineering, 2010)
Lithuanian public e-services at the level of municipalities are lagging behind the level of the central authorities. This is due to many factors, which leads to a slight lack of good position. A large proportion of the municipal authorities do not have e-service development strategies, or governing documents by the activities of the virtual space. It should be noted that this situation is in the part of central authorities too. This leads to the situation that the strategy aims are not fully realized. Although individual government institutions have been successful and effectively developing e-services, e.g. the State Tax Inspectorate is at the fifth level of public service. In order to improve the needs of society and citizens, a public service list was formed, whose services should be transferred as soon as possible to the virtual space, and provided with the levels of public e-services. The implementation of established goals can expect significant improvement in this area. Important, but still weak-moved to the virtual space of the public service areas is the environmental area. There has been no public e-service concept of environmental area in Lithuania yet. The article describes models of public e-services in the field of waste management. Article in Lithuanian. Elektroninė valdžia Lietuvoje: savivaldos pjūvis